Differences In Islamic Economy, Socialist Economy and Capitalist Economy - Nursaid, Nursaid (Revenue Journal: Management and Entrepreneurship, 2024)
This study explores the fundamental differences between the Islamic economy, socialist economy, and capitalist economy, focusing on their theoretical foundations, conceptual frameworks, and methodological approaches. The research is motivated by the need to understand how these economic systems respond to global economic challenges and their implications on social equity and resource distribution. The study employs a qualitative research design, analyzing data through comparative analysis of relevant literature, historical documents, and expert interviews. Data collection techniques include document analysis and semi-structured interviews with economists and scholars specialized in these fields. The findings reveal that the Islamic economy emphasizes ethical investment and social justice, guided by Sharia principles, while the socialist economy prioritizes collective ownership and egalitarian distribution of wealth. In contrast, the capitalist economy is driven by market forces and individual profit maximization, often leading to significant social and economic inequalities. The research concludes that each system has unique strengths and weaknesses, contributing differently to economic stability and social welfare. Key findings include the Islamic economy's focus on moral values, the socialist economy's emphasis on social equality, and the capitalist economy's innovation and efficiency. The study contributes to the existing literature by providing a nuanced understanding of these economic systems and offering insights into their potential synergies.